S/MARt DB: a database on scaffold/matrix attached regions - Liebich, Ines (Oxford University Press, 2002)
S/MARt DB, the S/MAR transaction database, is a relational database covering scaffold/matrix attached regions (S/MARs) and nuclear matrix proteins that are involved in the chromosomal attachment to the nuclear scaffold. The data are mainly extracted from original publications, but a World Wide Web interface for direct submissions is also available. S/MARt DB is closely linked to the TRANSFAC database on transcription factors and their binding sites. It is freely accessible through the World Wide Web (http://transfac.gbf.de/SMARtDB/) for non-profit research.